2015
DOI: 10.1039/c4ta06593j
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic and stable mesoporous polymeric adsorbent for siloxane removal: D4 super-adsorbent

Abstract: Synthesis of a new class of siloxane adsorbent (D4) was done to purify methane-rich gases including biogas and digester gas, at near ambient temperature and atmospheric pressure. The nanoporous polymeric adsorbent with controlled wettability was successfully prepared under solvothermal conditions. Imidazole groups were introduced into the samples by copolymerization of divinylbenzene (DVB) with 1vinylimidazole (VI). The copolymer composition was varied to obtain optimum adsorption performance.Low-cost PDVB and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Previously, PDVB based polymers have been synthesized with various morphologies and textural properties including monodispersed microspheres [58], macroporous [59], nanoporous sheets [60] and as mesoporous materials [61]. Biogas purification from siloxane impurities has been conducted by highly hydrophobic mesoporous PDVB based materials [61,62].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, PDVB based polymers have been synthesized with various morphologies and textural properties including monodispersed microspheres [58], macroporous [59], nanoporous sheets [60] and as mesoporous materials [61]. Biogas purification from siloxane impurities has been conducted by highly hydrophobic mesoporous PDVB based materials [61,62].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, PDVB based polymers have been synthesized with various morphologies and textural properties including monodispersed microspheres [58], macroporous [59], nanoporous sheets [60] and as mesoporous materials [61]. Biogas purification from siloxane impurities has been conducted by highly hydrophobic mesoporous PDVB based materials [61,62]. The effect of synthesis parameters such as various solvent effects (type and ratio of solvent mixture), [63] synthesis temperature, [64] and initiator amount [65] have also been studied on textural properties of PDVB-based materials.…”
Section: Introductionmentioning
confidence: 99%
“…Figure showed that the N 2 adsorption–desorption isotherm revealed the similar properties of MIPs and NIPs in the profile curves. The shapes of the MIPs and NIPs N 2 adsorption–desorption isotherm were a mixture of types III and IV with hysteresis loop ( p / p 0 > 0.85), which indicated that MIPs and NIPs have microporous structures . In addition, the volume of N 2 adsorbed to MIPs was ≈100 mL g −1 , which was double than that of NIPs (50 mL g −1 ), indicating that MIPs had numerous imprinted cavities and should have higher surface area and pore volume.…”
Section: Resultsmentioning
confidence: 97%
“…The shapes of the MIPs and NIPs N 2 adsorption-desorption isotherm were a mixture of types III and IV with hysteresis loop (p/p 0 > 0.85), which indicated that MIPs and NIPs have microporous structures. [33] In addition, the volume of N 2 adsorbed to MIPs was ≈100 mL g −1 , which was double than that of NIPs (50 mL g −1 ), indicating that MIPs had numerous imprinted cavities and should have higher surface area and pore volume. The BET surface area and average pore size of MIPs were 106.01 m 2 g −1 and 1.70 nm, respectively, which were only slightly different from those of NIPs (102.61 m 2 g −1 and 1.67 nm; Table S2, Figure S3, Supporting Information).…”
Section: Preparation Of Mipsmentioning
confidence: 95%
“…Among these methods, adsorption technology is regarded as one of the most promising methods due to its high efficiency, low cost, and facile operation. Up to now, a number of materials including active carbon (Choy, Porter, & McKay, ; Dias, Alvim‐Ferraz, Almeida, Rivera‐Utrilla, & Sánchez‐Polo, ; Kadirvelu, Karthika, Vennilamani, & Pattabhi, ; Li, Liu, & Zhu, ; Maneerung et al, ; Sharma & Upadhyay, ; Tan, Hameed, & Ahmad, ), zeolite (Delkash, Bakhshayesh, & Kazemian, ; Noroozifar, Khorasani‐Motlagh, & Naderpour, ; Wang & Peng, ), resin (Han et al, ; Jafari, Noshadi, Khakpash, & Suib, ; Jia & Liu, ; Li, Wu, et al, ; Li, Wang, Zhang, Liang, & Sun, ; Wu, Zhang, Li, & Wang, ; Yang, Han, Du, Luo, & Wang, ), and MOF (Dias & Petit, ; Huo & Yan, ; Lin et al, ; Yan et al, ; Zhao et al, ) have been explored for the removal of dye. MOFs as adsorbents have been extensively investigated due to their high porosities and specific interactions between adsorbate and adsorbent (Dias & Petit, ).…”
Section: Introductionmentioning
confidence: 99%